Meta-Analysis: The preferred method of choice for the assessment of distance learning quality factors - Shachar, Mickey (International Review of Research in Open and Distributed Learning, 2008)
Current comparative research literature, although abundant in scope, is inconclusive in its findings, as to the quality and effectiveness of distance education versus face-to-face methods of delivery. Educational research produces contradictory results due to differences among studies in treatments, settings, measurement instruments, and research methods. The purpose of this paper is to advocate the use of a meta-analytic approach by researchers, in which they synthesize the singular results of these comparative studies, by introducing the reader to the concept, procedures, and issues underlying this method. This meta-analytic approach may be the best method appropriate for our ever-expanding and globalizing educational systems – in general, crossing over geographical boundaries with their multiple languages, and educational systems in particular. Furthermore, researchers are called to contribute to a common database of distance learning factors and variables, from which future researchers can share, glean, and extract data for their respective studies.